2022
DOI: 10.3390/ijms23179591
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 2 (IGF-2) and Insulin-like Growth Factor Binding Protein 7 (IGFBP-7) Are Upregulated after Atypical Antipsychotics in Spanish Schizophrenia Patients

Abstract: Insulin-like growth factor 2 (IGF-2) and IGF binding protein 7 (IGFBP-7) have been related to schizophrenia (SZ) due to their implication in neurodevelopment. The purpose of this study was to assess whether the alterations in IGF-2 and IGFBP-7 in SZ patients are intrinsically related to the psychiatric disorder itself or are a secondary phenomenon due to antipsychotic treatment. In order to test this hypothesis, we measured plasma IGF-2 and IGFBP-7 in drug-naïve first episode (FE) and multiple episodes or chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
0
7
1
Order By: Relevance
“…One study conducted in Spain found that there was no significant difference in IGF-1 levels between first-psychotic episode BD patients and controls neither at baseline nor after 1, 6, and 12 months of treatment ( Palomino et al, 2013 ). Although we could not study first-episode BD patients, we had previously showed that both IGF-2 and IGFBP-7 were significantly increased in first-episode SZ Spanish patients ( Fernández-Pereira et al, 2022 ). Curiously, during the first psychotic episode, the levels of IGF-1 in SZ patients were significantly higher than those in BD patients but not in controls ( Palomino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study conducted in Spain found that there was no significant difference in IGF-1 levels between first-psychotic episode BD patients and controls neither at baseline nor after 1, 6, and 12 months of treatment ( Palomino et al, 2013 ). Although we could not study first-episode BD patients, we had previously showed that both IGF-2 and IGFBP-7 were significantly increased in first-episode SZ Spanish patients ( Fernández-Pereira et al, 2022 ). Curiously, during the first psychotic episode, the levels of IGF-1 in SZ patients were significantly higher than those in BD patients but not in controls ( Palomino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, to the best of our knowledge, no study has yet evaluated peripheral IGF-2 levels in BD patients. Our group previously reported that the plasma levels of IGF-2 were significantly increased in chronic patients of related psychiatric disorders such as schizophrenia (SZ) ( Fernández-Pereira et al, 2022 ) and major depressive disorder (MDD) ( Fernández-Pereira et al, 2023 ) during either a psychotic or a depressive episode, and those levels were normalized after a period of treatment with antipsychotics or antidepressants, respectively. From our perspective, exploring the peripheral relation of inflammatory markers and IGF proteins could be of interest in BD patients.…”
Section: Introductionmentioning
confidence: 99%
“…2023, 24, 1891 2 of 20 response to at least two sequential non-clozapine antipsychotic trials of sufficient dose, duration, and adherence [6]. Patients with TRS have higher rates of substance abuse, early cognitive decline, and higher rates of suicide ideation [7][8][9][10]. As pharmacological and therapeutic approaches differ between SZ and TRS [11][12][13][14], early identification of the resistance condition is essential for a rapid and effective pharmacological intervention, limiting damage to the patient and their environment and improving the adherence to treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of psychiatric disorders, IGF-2 peripheral levels have been previously studied in schizophrenia [29][30][31][32] and in neurodegenerative disorders that impair memory or cognitive status, such as Alzheimer's disease [33][34][35], Huntington's disease [36] and Parkinson's disease [37]. However, to the best of our knowledge, there is no literature available on IGF-2 peripheral levels in major depressive disorders involving human samples.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, peripheral IGF-1 has received far more attention in the last few decades, not just in depression [38][39][40][41][42][43][44][45][46][47][48][49], but also in other mental conditions such as schizophrenia [29,[49][50][51][52][53][54][55][56] and bipolar disorder [57][58][59][60][61][62]. On the other hand, circulating IGFBPs have been less widely studied than their ligand counterparts in the field of psychiatry, and always in a context of their IGF-dependent actions [29][30][31][32]38,55,[63][64][65]. Some IGFBPs have received more attention than others.…”
Section: Introductionmentioning
confidence: 99%